A test of the stranger-interviewer norm in the Dominican Republic. (2nd January 2016) - Sana, Mariano; Stecklov, Guy; Weinreb, Alexander A.
Abstract : We offer the first empirical test of the 'stranger-interviewer norm', according to which interviewers in social, demographic, and health surveys should be strangers—not personally familiar with respondents. We use data from an experimental survey in the Dominican Republic that featured three types of interviewer: from out of town (outsiders); local but unknown to the respondent (local-strangers); and local with a previous relationship to the respondent (insiders). We were able to validate answers to up to 18 questions per respondent, mainly by checking official documents in their possession. Contrary to expectations derived from the stranger-interviewer norm, respondents were more reluctant to show the documents needed for validation when the interviewer was an outsider. Furthermore, and again at odds with the stranger-interviewer norm, we found no difference in accuracy by type of interviewer. Our results have important implications for the selection of survey interviewers in less developed and non-Western settings.